East Asia Update, November 2002 : Making Pogress in Uncertain Times - World Bank (World Bank, Washington, DC, 2020)
This report is written at a time when the East Asia region - having enjoyed a powerful economic rebound in the first half of 2002 is now affected by strong cross-currents and uncertainties in both its external environment and its domestic setting. Within the region, the terrorist attacks at Bali and elsewhere in the region will depress tourism and business confidence, at least for a time, taking a toll on the near term growth outlook for Indonesia in particular. Economic and structural reforms will increasingly have to share policymakers' crowded agendas with security concerns, as well with a political focus on elections that are coming up in several countries in the next 1-2 years. This year's recovery has been powered by exports, private consumer spending, and, in some cases, fiscal stimulus, but private investment spending has generally remained weak. Hopes that growth by itself would take care of excessive corporate leverage and distressed debt in the region have not been met. Debt-equity ratios, though they have fallen in some instances, remain high by international standards in most cases, and, together with low corporate profitability, continue to depress the investment climate and undermine the prospects for accelerated medium term growth. East Asian countries can make progress even in these uncertain times by continuing to lay stress on some core fundamentals. Improving law and order and public security is essential for both economic development and the consolidation of mo re consensual or representative government. East Asian countries have weathered recent external shocks quite well because of their more robust external finances. Careful, prudent macroeconomic management of both external and domestic fiscal positions will continue to pay high dividends in the present volatile global economic and financial environment. But sound fiscal management has to be married with the need to pay for the high quality public services that increasingly sophisticated East Asian societies demand. Efforts to strengthen governance, administration, and public financial accountability are therefore critical. Finally, achieving medium term growth entails tapping the energies of private individuals, entrepreneurs and firms big and small. Completing the restructuring agenda left over from the financial crisis, improving financial sector supervision and regulation, and undertaking broader reforms to strengthen the investment climate are all important in this regard.